Origin of Hepatitis Delta Virus mRNA - Gudima, Severin (American Society for Microbiology, 2000)
Hepatitis delta virus (HDV) is unique relative to all known animal viruses, especially in terms of its ability to redirect host RNA polymerase(s) to transcribe its 1,679-nucleotide (nt) circular RNA genome. During replication there accumulates not only more molecules of the genome but also its exact complement, the antigenome. In addition, there are relatively smaller amounts of an 800-nt RNA of antigenomic polarity that is polyadenylated and considered to act as mRNA for translation of the single and essential HDV protein, the delta antigen. Characterization of this mRNA could provide insights into the in vivo mechanism of HDV RNA-directed RNA transcription and processing. Previously, we showed that the 5′ end of this RNA was located in the majority of species, at nt 1630. The present studies show that (i) at least some of this RNA, as extracted from the liver of an HDV-infected woodchuck, behaved as if it contained a 5′-cap structure; (ii) in the infected liver there were additional polyadenylated antigenomic HDV RNA species with 5′ ends located at least 202 nt and even 335 nt beyond the nt 1630 site, (iii) the 5′ end at nt 1630 was not detected in transfected cells, following DNA-directed HDV RNA transcription, in the absence of genome replication, and (iv) nevertheless, using in vitro transcription with purified human RNA polymerase II holoenzyme and genomic RNA template, we did not detect initiation of template-dependent RNA synthesis; we observed only low levels of 3′-end addition to the template. These new findings support the interpretation that the 5′ end detected at nt 1630 during HDV replication represents a specific site for the initiation of an RNA-directed RNA synthesis, which is then modified by capping.